Industrial dominance: the theory and the methods of diagnosis - M. V. Pyatkov; G. D. Boush (Вестник СибАДИ, 2017)
The results of industrial dominance’ theoretic research and the methods of diagnosis are presented. According to the authors, the impact of industrial dominance lies in the sphere of decreasing the firm’s access to agglomeration effects. The basic conditions which are needed for the emergence of industrial dominance are presented. The author presents the way to diagnose existence of industrial dominance along with the method of measuring the influence of industrial dominance within a particular industry. The results presented by the authors will help to form effective economic policy for industries where industrial dominance is presented.